Studi komparasi penerimaan pajak sebelum dan sesudah adanya covid-19 untuk peningkatan penerimaan pajak (studi kasus di KPP Pratama Batu) - Aris Wahyudi; Dwi Orbaningsih; Kohar Adi Setia (Jurnal Ilmiah Bisnis dan Perpajakan (Bijak), 2023)
Taxes are state revenues that are used as the main source of the state. Covid-19 is a disease that has become a pandemic in mid-2019 which has paralyzed several sectors, one of which is the economy. The many rules that were set during the pandemic paralyzed tax revenues. Various efforts have been made by the government to survive during the pandemic by providing tax incentives which have an impact on tax revenues. The purpose of this study is to find out the comparison of tax revenue before and after Covid-19. This research is using qualitative method. Data was taken through interview techniques which were conducted with 3 informants at KPP Pratama Batu. The results of the study show that there are differences in terms of targets and also tax revenue before and after the pandemic. In 2020 the government lowered the target because it saw the sluggish economy, but the hard work efforts were still carried out. This can be seen from the comparison of the percentage of realized tax revenue before and after the pandemic did not drop drastically.